ESTABLISHMENT OF ENHANCED ANTHOCYANIN PRODUCTION IN MALVA SYLVESTRIS L. WITH DIFFERENT INDUCED STRESS - JAYALAKSHMI N.R; THARA SARASWATHI K.J.; VIJAYA B.; RAMAN D.N.S.; SURESH R (International Journal of Pharma and Bio Sciences, 2012)
A comparative study in Malva sylvestris L. plants was carried out for change in growth pattern and their anthocyanin production with various induced stress. Exogenous administration of 0.1mM concentration of abscisic acid, silver nitrate as foliar spray for five successive days and supplemental thirty minutes exposure dose of UV-B for continuous three days to the plants significantly induced variation in the growth pattern and anthocyanin content. The abscisic acid and silver nitrate treatment induced increased anthocyanin content up to five fold and three fold with induced morphological variations by increasing height, leaf mass, leaf number, fresh and dry weight in comparison to untreated plants whereas the plants with UV-B treatment showed reduced growth with two fold increase in anthocyanin content. The result of the study using biological (abscisic acid), chemical (silver nitrate) and physical (UV-B) stress evidenced both positive and negative responses with induction of high anthocyanin production and varied growth pattern.